Contribution to the Dermestidae (Coleoptera) of Thailand with description of two new species - Kadej, Marcin; Háva, Jiří (Zootaxa, 2016)
The following new species from Thailand are described, illustrated and compared with related species: Anthrenus (Nathrenus) herrmanni sp. nov., and Adelaidia thailandica sp. nov. A differential diagnosis as well as additional faunistic records are provided. A new faunistic record for Trinodes tonkineus Pic, 1922 is given.
Keywords: zvířata; druhová specificita; Animals; Female; Thajsko; Male; Thailand; mužské pohlaví; ženské pohlaví; Coleoptera; Species Specificity; brouci